1998
DOI: 10.1523/jneurosci.18-16-06059.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicular Localization and Exocytosis ofl-Aspartate in Excitatory Nerve Terminals: A Quantitative Immunogold Analysis in Rat Hippocampus

Abstract: To elucidate the role of aspartate as a signal molecule in the brain, its localization and those of related amino acids were examined by light and electron microscopic quantitative immunocytochemistry using antibodies specifically recognizing the aldehyde-fixed amino acids. Rat hippocampal slices were incubated at physiological and depolarizing [K ϩ ] before glutaraldehyde fixation. At normal [K ϩ ], aspartate-like and glutamatelike immunoreactivities were colocalized in nerve terminals forming asymmetrical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 51 publications
(73 reference statements)
9
125
1
Order By: Relevance
“…[1][2][3][4][5][6][7]). Strongly in favour of an exocytotic release mechanism are our previous immunocytochemical results showing that K + induced depolarisation elicited depletion of L-aspartate from nerve endings, which could be inhibited by low extracellular Ca 2+ -concentrations and tetanus toxin [8][9][10]. In addition, Daspartate has been shown to be subject to exocytotic release both from cultured neurons [11] There is ample evidence that excitatory nerve endings in the brain contain functional plasma membrane excitatory amino acid transporters (EAATs) [16][17][18][19][20].…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7]). Strongly in favour of an exocytotic release mechanism are our previous immunocytochemical results showing that K + induced depolarisation elicited depletion of L-aspartate from nerve endings, which could be inhibited by low extracellular Ca 2+ -concentrations and tetanus toxin [8][9][10]. In addition, Daspartate has been shown to be subject to exocytotic release both from cultured neurons [11] There is ample evidence that excitatory nerve endings in the brain contain functional plasma membrane excitatory amino acid transporters (EAATs) [16][17][18][19][20].…”
Section: +mentioning
confidence: 97%
“…Hippocampal slice experiments were performed as previously described [8,9,18]. In brief, in each experiment we…”
Section: Hippocapal Slice Incubationmentioning
confidence: 99%
“…Aspartate immunoreactivity has been localized to synaptic vesicles of certain excitatory [10,11] and inhibitory [12] hippocampal pathways. In those pathways, aspartate immunoreactivity was associated with synaptic vesicles to the same degree as glutamate or GABA immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to methodological differences between the two studies, however, further investigations are needed to substantiate the implied physical separation of aspartate and glutamate release sites. The colocalization of vesicular aspartate with vesicular glutamate in synaptic terminals of certain excitatory hippocampal pathways [10,11,13] and its colocalization with vesicular GABA in others [12] suggests a physiological role for aspartate different from that of other transmitter amino acids. We suggested that aspartate release at a distance from the presynaptic active zones should activate extrasynaptic NMDA receptors and that aspartate may indeed be a major endogenous agonist for these receptors [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation